Sanitary-Epidemiological Welfare Provision in the Preparations to and Management of the “G-20” Summit in Saint-Petersburg, 2013. Communication 1. Epidemiological Risks and Core Operations for Sanitary-Epidemiological Welfare Provision in the Preparations to the Summit - G. G. Onishchenko (Проблемы особо опасных инфекций, 2013)
Established are the basic principles of sanitary-epidemiological welfare provision in the preparations to and managing of the public event by the example of “G-20” Summit. Outlined is the significance and essentiality of epidemiological risk assessment. Specified are the areas of priority as regards anti-epidemic activities in the run-up period. Established is the priority of epidemiological surveillance and laboratory control over the places of residence of participants, caterers and supplying companies, and public catering facilities.